The influence of the fire temperature on the condition of steel roof structure. (April 2023) - Mackiewicz, M.; Krentowski, J.R.; Knyziak, P.; Kowalski, R.
Highlights: Assessment of structure damages caused by accidental fire load is a complex process. Determining temperature range decides of reusing the structural elements after repair. Assumption of the fire scenario and temperature range is crucial. Decisions of reusing undamaged components should be justified by in-depth analysis. Designing and reconstruction of facilities should take into account fire protection. Abstract: Contemporary process of structure designing takes into account the requirements for the structural load-bearing capacity, parameters in terms of serviceability, as well as safety and resistance in the case of fire occurrence. The fire protection required by law does not guarantee full resistance, but only the safety of the integrity of the structure subjected to fire over a certain period of time. Structures after a fire are assessed in terms of their further use. A special case is the partial damage to the structure of some load-bearing elements, including their separate elements. The research issue is the assessment of the structure both as a whole and as individual components. Usually some elements have to be replaced and some can be used directly or after strengthening. This issue has been discussed in the article. Fire in the sports hall building developed as a result of improper use of the ventilation system. The range and effects of fire affected some of the structural elements. An assessment of the fire consequences was carried out, numerical analyzes were performed and the results were compared with accurate measurements of the structure deformation. The obtained conclusions allowed to determine the impact of the fire on the structural elements and the procedure for the repair of the damaged facility. Some elements, mainly the roof covering, had to be replaced, and the main elements of the structure were strengthened to ensure the required level of safety.